Residential steel framing handbook - Scharff, Robert (McGraw-Hill, 1996)
The steel frame "how-to'' for wood-builders. The use of steel in residential construction is hot. So if your expertise lies in conventional wood frame construction, you'll definitely want to pick up the Residential Steel Framing Handbook. Robert Scharff and the editors of Walls & Ceilings Magazine take you step-by-step through each stage of the construction process--from preconstruction preparation to interior finishing--delivering all the in's and out's of building houses with steel. Jam-packed with over 350 illustrations and photographs, it's the perfect on-the-job training manual for you and your crew: sound proofing; insulation; calculating load strength; special tools and equipment; drywall and other interior finishes; building codes and zoning regulations; material specifications and selection; connectors and fasteners; steel floor framing; stell framed roofs; and much more.